2018
DOI: 10.1016/j.lindif.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-efficacy, growth mindsets, and university students' integration in academic and social support networks

Abstract: Combining complete social networks and structural equation modeling, we investigate how two learning-related cognitions, academic self-efficacy and growth mindsets, relate to integration in support networks of 580 university students in 30 seminar groups. We assessed integration as popularity in academic support networks (being an academic helper and collaborator) and in social support networks (being a friend and resource for sharing personal difficulties). Perceived integration in both networks was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 73 publications
(103 reference statements)
1
72
1
9
Order By: Relevance
“…Alternatively, students may not be aware of the potential nominations of their classmates. Future studies could include students’ meta-perceptions of themselves as a source of academic help for their peers (cf., Zander et al, 2018 ). Combining proximal and distal measures of social persuasion could facilitate our understanding of whether it is more important to girls’ self-efficacy beliefs how much persuasion they think they receive versus how much persuasion they actually receive from their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, students may not be aware of the potential nominations of their classmates. Future studies could include students’ meta-perceptions of themselves as a source of academic help for their peers (cf., Zander et al, 2018 ). Combining proximal and distal measures of social persuasion could facilitate our understanding of whether it is more important to girls’ self-efficacy beliefs how much persuasion they think they receive versus how much persuasion they actually receive from their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interesting findings revealed that learners with growth mindset play an important role in developing good citizenship by Waithaka et al [56], Cooley and Larson [46], Nolder and Kadous [57], and Zander et al [58] pointed out that students with a growth mindset have a clear tendency towards learning attitude, appreciation of learning, and happiness in various learning. Caniëls et al [59], and Han et al [39] revealed that a growth mindset has a tendency to stimulate the students with an awareness of maintaining public interest, having a public mind, and being volunteer activities for society.…”
Section: Growth Mindsetmentioning
confidence: 99%
“…Although the link between teaching mindsets and emotions has not been explored, research on students provides indirect support for our hypothesis. Students with a growth mindset tend to be more self-efficacious, and their belief that they can improve their competence leads to more positive emotions (King et al 2012;Zander et al 2018). In turn, teachers with higher positive emotions are more likely to be engaged in their work (Bakker and Demerouti 2007).…”
mentioning
confidence: 99%